PENGOLAHAN BUAH PEDADA MENJADI SIRUP DAN PUPUK ORGANIK DI KAWASAN WISATA CIGIMBAL PARK KABUPATEN CILACAP - Nurlinda Ayu Triwuri; Theresia Evila Purwanti Sri Rahayu; Oto Prasadi; Annisa Yuliana Angeline; Nur Indah Wardani; Murni Handayani; Ilma Fadlilah (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2026)
The mangrove forest in Cilacap Regency, Central Java, is located in the Cigimbal Park area of ??Tritih Kulon Village. Mangroves grow in river mouths or estuaries, where organic sediment and mud are collected. One type of mangrove, namely pedada fruit (Sonneratia alba), contains flavonoids, terpenoids, tannins, phenolics, steroids, and other bioactive compounds that function as antioxidants. The implementation method of community service activities consists of socialization and training stages. Based on the content of pedada fruit, pedada fruit processed into syrup also has nutritional content such as 1.20% protein, 0.20% fat, 3.50% carbohydrates, and 55.30% vitamin C. The storage time of pedada syrup at room temperature lasts for 7 days, if at a cold temperature of 4oC lasts for 30 days. In addition, the residue from pedada syrup production in the form of pedada skin, petals and dregs can be processed into organic fertilizer. The decomposition period of organic material is added with effective microorganisms 4 for 28 days, until it is black and odorless.